Growth of Sessile Sphaerotilus natans in a Tubular Recycle System - McCoy, William F. (1982)
The growth of sessile Sphaerotilus natans was measured in a continuous-flow recycle system. Four methods were used to confirm that the growth of the biofilm was a linear function that increased with time. Of the methods used, one monitored in situ biofouling (increased fluid frictional resistance), two indicated biomass (ATP and DNA per square centimeter), and one allowed the direct observation of replaceable test surfaces by scanning electron microscopy. The filamentous growth of S. natans caused an increase in the fluid frictional resistance. The increase in biofouling was directly proportional to the increase in biomass.